THERMOBAROMETRY OF METAMORPHOSED PSEUDOTACHYLYTE AND DETERMINATION OF SEISMIC RUPTURE DEPTH DURING DEVONIAN CALEDONIAN EXTENSION, NORTH NORWAY - Leib, Susan E. (UKnowledge, 2013)
Crustal faulting has long been known as the source of shallow seismicity, and the seismogenic zone is the depth (3-15 km) within the crust that is capable of co-seismic slip, largely under brittle conditions. However, some continental seismicity occurs at depths >> 15 km. I performed thermobarometry of mylonitic pseudotachylyte to determine the P-T of a seismogenic extensional fault in the Caledonian Norwegian margin. Two shear zones (Eidsfjord and Fiskfjord) located in northern Norway exhibit brittle extension propagating into the ductile regime of the lower crust as evidenced by the presence of pseudotachylyte. Averages from Eidsfjord (653 ± 38°C and 570 ± 115 MPa) and Fiskfjord (680 ± 70°C and 1121 ± 219 MPa) correspond to depths of co-seismic slip of 21 ±4 km and 41 ± 9 km, respectively. These depths are 5-25 km below the depth of the standard seismogenic zone in mature fault systems, and require another mechanism (e.g. dynamic downward rupture, unusually high shear stresses) to account for seismogenic rupture at such depths. Assuming Eidsfjord and Fiskfjord were uplifted at the same time, and considering they are currently at the same crustal level, Fiskfjord was uplifted a greater amount and at a faster rate as it was initially located at a greater crustal depth.